Tourism Development Patterns In An Effort To Attract Tourists As A Challenge In The Next Normal Era: Case Study On Mgm Jeep Lava Tour Yogyakarta - Nur Umi Putri Augustin; Yustina Denik Risyanti; Ester Wulandari (International Conference On Digital Advanced Tourism Management And Technology, 2023)
During the Next Normal era, Indonesian people are very free to carry out daily activities such as work, vacations and long-term interactions. This also has an impact on tourist visits to the Jeep Lava Tour, of course with trends in tourist behavior that have changed. Tourists tend to choose outdoor tours such as the Lava Tour, where tourists don't want to gather for too long in a closed place. Management efforts not only include setting health protocols, but also various other aspects such as developing tourist experiences, interaction with local communities, and strategies for handling increased tourist visits. The aim of this research is to find out and describe the management and development patterns of the MGM Jeep Lava Tour in the next normal era in an effort to attract tourists. The method used in this research is qualitative method. The results of research on the management and development patterns of MGM's Jeep Lava Tour in the next normal era, namely innovation in the tourist experience and maximizing coordination with the use of technology in operations are key components. Collaboration with related parties maintains the sustainability of destinations and provides positive benefits for the environment and society.